Proactive vs. reactive order-fulfillment resource allocation for sea-based logistics. (June 2018) - Mofidi, Seyed Shahab; Pazour, Jennifer A.; Roy, Debjit
Highlights: Multiple SKUs with varying unit fulfilment costs captured with an activity profile. Model internal cargo flow processes in a sea-based logistics environment. Extend the newsvendor literature by studying negative marginal shortage costs. Determine the subset of SKUs for optimal proactive strategy. High-demanded items may not always be beneficial for a proactive strategy. Abstract: We study proactive and reactive sea-based order-fulfillment decisions for a set of SKUs. In such systems, a proactive strategy may be more costly than a reactive strategy and variable marginal costs change with respect to an activity profile. We derive the optimal sets of SKUs and their quantities to handle prior (proactive strategy) or after (reactive strategy) demand materializes. Counterintuitive results show the proactive set may not necessarily include the high-demanded SKUs. This work extends the newsvendor model by analyzing negative marginal shortage costs. The model is illustrated with historical data from a sea-based logistics military application.